أهمية السياسة الشـــرعية من منظور القرآن - ahmad ridho (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2014)
As an agreement of Muslim’s ummah that Islamic politic is a necessity, because of it is flexibility and comprehensive and can accommodate a development in contemporary life. The goal is to manage the affairs of the Muslims, both internally and externally in accordance with the teachings of the Qur’an. As well as it aims to prove that the teachings of Islam is compatible to perform a justice in regulating a good citizens, and set up an organization and public institutions to serve peoples in the community securely and peaceful. It happened because of political Islam consistently seeks to go hand in hand with social development at any time as well as the general principles of Islam.